Beginning data science, IoT, and AI on single board computers : core skills and real-world application with the BBC micro:bit and XinaBox - Meitiner, Philip; Seneviratne, Pradeeka (Technology in action series., 2020)
Learn to use technology to undertake data science and to leverage the Internet of Things (IoT) in your experimentation. Designed to take you on a fascinating journey, this book introduces the core concepts of modern data science. You'll start with simple applications that you can undertake on a BBC micro:bit and move to more complex experiments with additional hardware. The skills and narrative are as generic as possible and can be implemented with a range of hardware options. One of the most exciting and fastest growing topics in education is data science. Understanding how data works, and how to work with data, is a key life skill in the 21st century. In a world driven by information it is essential that students are equipped with the tools they need to make sense of it all. For instance, consider how data science was the key factor that identified the dangers of climate change -- and continues to help us identify and react to the threats it presents. This book explores the power of data and how you can apply it using hardware you have at hand. You'll learn the core concepts of data science, how to apply them in the real world and how to utilize the vast potential of IoT. By the end, you'll be able to execute sophisticated and meaningful data science experiments - why not become a citizen scientist and make a real contribution to the fight against climate change. There is something of a digital revolution going these days, especially in the classroom. With increasing access to microprocessors, classrooms are are incorporating them more and more into lessons. Close to 5 million BBC micro:bits will be in the hands of young learners by the end of the year and millions of other devices are also being used by educators to teach a range of topics and subjects. This presents an opportunity: microprocessors such as micro:bit provide the perfect tool to use to build 21st century data science skills. Beginning Data Science and IoT on the BBC micro:bit provides you with a so lid foundation in applied data science. You will: · Use sensors with a microprocessor to gather or "create" data · Extract, tabulate, and utilize data it from the microprocessor · Connect a microprocessor to an IoT platform to share and then use the data we collect · Analyze and convert data into information